South Africa's implementation of the European Community Regulation to combat illegal, unreported and unregulated fishing - Frantz, Theressa Rosetta (Centre for Law and Society, 2026)
Illegal, unreported and unregulated (IUU) fishing has become a worldwide challenge facing fisheries in the 21st century. IUU fishing has the effect of undermining existing management and conservation measures at a national, regional or international level. In addition, IUU also defeats the purpose of stock rebuilding initiatives, thereby resulting in untold economic, social and ecological losses, making sustainable use an impossible goal.